2014
DOI: 10.1007/s10534-014-9810-z
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of total iron in Helicobacter pylori-infected gastric epithelial cells

Abstract: Despite the evidence suggesting a role for Helicobacter pylori in the induction of systemic iron deficiency anaemia, little is known about the possibility of infection-associated changes in cellular iron homeostasis at the gastric epithelium. In this study we compared four different techniques for measuring iron in AGS cells, a gastric epithelial cell line that is widely used to model to H. pylori infection in vitro. Inductively coupled plasma-mass spectrometry proved to be an efficient method, but only when l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The iron concentration of the resultant solution was measured from the absorbance of the Fe 2+ - ferrozine complex at 564 nm (ε 564 = 27.9 mM −1 cm −1 ) using a Varian-Cary 50 Bio UV-vis spectrophotometer, normalized by cell population and reported as Fe atoms/CFU. The colorimetric determination of total intracellular iron using ferrozine offers a sensitive, accurate and low cost analytical technique, 33,34 which has been shown to produce results similar to those obtained by atomic absorption spectrometry. 35 …”
Section: Methodsmentioning
confidence: 95%
“…The iron concentration of the resultant solution was measured from the absorbance of the Fe 2+ - ferrozine complex at 564 nm (ε 564 = 27.9 mM −1 cm −1 ) using a Varian-Cary 50 Bio UV-vis spectrophotometer, normalized by cell population and reported as Fe atoms/CFU. The colorimetric determination of total intracellular iron using ferrozine offers a sensitive, accurate and low cost analytical technique, 33,34 which has been shown to produce results similar to those obtained by atomic absorption spectrometry. 35 …”
Section: Methodsmentioning
confidence: 95%
“…H . pylori infection increases the amount of iron in AGS cells, perturbing intracellular iron homeostasis [ 17 ]. In vivo studies have also shown that gastric Helicobacter infection alters iron status in mouse and gerbil models [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent observation of increased total iron in H . pylori -infected AGS gastric epithelial cells that is independent of the extracellular iron concentration supports this hypothesis [ 9 ].…”
Section: Introductionmentioning
confidence: 79%
“…An infection-associated increase in total iron levels seen when H . pylori are added to cultured gastric AGS cells [ 9 ], which was not a result of bacterial association with the cells ( S2 Fig ), suggested that H . pylori may perturb iron uptake and/or storage mechanisms involved in maintaining cellular iron homeostasis.…”
Section: Resultsmentioning
confidence: 99%